Mixed classes: an experience from the perspective of the students' learning m otors and social skills. (Revista horizonte, 2014)
This investigation's main objective was to analyze the faculty member’s opinion about the effects of the mixed (women and men) Physical Education (PE) classes in the motor and social learning of the student body. The methodology of the investigation was a descriptive study, with a group of 328 individuals of Scientist-Humanist High School establishments, using for the collection of data a questionnaire Liket type, with a five options answer. The primary variable to be considered was the faculty members opinion about the mixed PE clases regarding the motor and social learning of the student body. The results indicate that 41.2 % of the teachers agree that mixed classes favors the learning of a greater variety of sports skills, being male teachers who have a more positive response, while female teachers only agreed to this criteria of mixed classes in a 15.2% . As a conclusion it can be said that coeducation is a practice that a significant number of female and male teachers have applied for several years now, although in some cases this coeducational model is not used widely in the PE classes.